contestada

5. A system of equations is below. For what value would
you multiply the first equation to eliminate the x-term?
(y=x+2
3x + 3y = 6

Respuesta :

Answer:

We would multiply the first equation by -3  to eliminate the x-term.

Step-by-step explanation:

Given the system of equations

y = x+2                Equation 1

3x+3y = 6           Equation 2

Multiply the Equation 1 by -3

-3y = -3(x+2) ⇒ -3y = -3x-6 ⇒ -3x+3y = 6

Thus, equation 1 becomes

-3x+3y = 6

Now, adding equation 2

-3x+3y = 6

+

3x+3y = 6

________

0x + 6y = 12

6y = 12

y = 2

Therefore, we would multiply the first equation by -3  to eliminate the x-term.